Modification of The Synthesis of Silica from Litter Ori Bambusa (Bambusa blumeana) Leaves Using Sodium and Potassium With The Hydrothermal Sol-Gel Method As Agricultural Fertilizer - Mahmudah Hamawi; Niken Trisnaningrum; Ilham Mufandi (Agroindustrial Technology Journal, 2023)
Bamboo plants in Indonesia are familiar plants and have not been utilized optimally. Most people only use the stems for daily needs and a small part for industry, while the leaves are left as waste. Bamboo leaves have a fairly high silica content. Bamboo leaves that have fallen and are scattered on the ground (bamboo leaf litter) are a potential source of natural silica. Silica fertilizer in agriculture is still very necessary, especially in nanosized. Through silica extraction from bamboo leaf litter, it is hoped that it will be able to meet agricultural silica needs and reduce bamboo leaf waste. The aim of this research is to modify the synthesis of silica from ori bamboo leaf litter (Bambusa blumeana) by extracting NaOH and KOH using the hydrothermal sol-gel method to produce nano silica. Nano silica production uses the hydrothermal method because it does not require large costs, is more effective, and has a high level of purity. Synthesis of original bamboo leaf litter silica using the hydrothermal sol-gel method. Bamboo leaf litter ash was analyzed using the XRF test, and silica was analyzed using the SEM-EDX mapping test to determine its morphology and content. The research results showed that synthesis with sodium produced higher levels of bamboo leaf silica compared to potassium. The size of the silica particles obtained is still in the form of micrometers (47–52 µm). Bamboo plants in Indonesia are familiar plants and have not been utilized optimally. Most people only use the stems for daily needs and a small part for industry, while the leaves are left as waste. Bamboo leaves have a fairly high silica content. Bamboo leaves that have fallen and are scattered on the ground (bamboo leaf litter) are a potential source of natural silica. Silica fertilizer in agriculture is still very necessary, especially in nanosized. Through silica extraction from bamboo leaf litter, it is hoped that it will be able to meet agricultural silica needs and reduce bamboo leaf waste. The aim of this research is to modify the synthesis of silica from ori bamboo leaf litter (Bambusa blumeana) by extracting NaOH and KOH using the hydrothermal sol-gel method to produce nano silica. Nano silica production uses the hydrothermal method because it does not require large costs, is more effective, and has a high level of purity. Synthesis of original bamboo leaf litter silica using the hydrothermal sol-gel method. Bamboo leaf litter ash was analyzed using the XRF test, and silica was analyzed using the SEM-EDX mapping test to determine its morphology and content. The research results showed that synthesis with sodium produced higher levels of bamboo leaf silica compared to potassium. The size of the silica particles obtained is still in the form of micrometers (47–52 µm).